Association between Dietary Fat Quality Index and Cardiovascular Diseases in Tabari Cohort population: A Cross-sectional Study - Sanaz Soltani; Mahmood Moosazadeh; Elahe Mohammadi (تحقیقات سلامت در جامعه)
Introduction and purpose: Studies on the relationship between the dietary fat quality index (FQI) and the risk of cardiovascular diseases (CVD) are very limited. Therefore, the present study was conducted with the aim of investigating the relationship between FQI and CVD risk among adults participating in the Tabari Cohort study. Methods: This cross-sectional study was conducted on 9,408 people aged 35 to 70 years who participated in the initial stage of the Tabari Cohort study. The usual food intake of the participants was evaluated using a semi-quantitative 118-item food frequency questionnaire. FQI was calculated using the relevant equation for all individuals, who were then classified based on quartiles of FQI score. A binary logistic regression test was used to investigate the relationship between FQI and CVD risk. Results: The mean (standard deviation) age of the participants in the study was 49.90 (9.31) years. The prevalence of CVD in the study population was 8.6% (807 people). The results of the crude model showed that there was no significant relationship between FQI score and CVD risk (odds ratio [OR]: 1.07; 95% confidence interval [CI]: 0.87-1.32). When this analysis was adjusted for a number of confounding factors, the association between FQI score and CVD risk remained non-significant (OR: 1.23; 95% CI: 0.97-1.55). Conclusion: No significant relationship was found between FQI score and CVD risk in the Tabari Cohort population. Further studies, especially with a prospective design, are recommended to investigate the relationship between dietary fat quality and CVD.